Cord Lining Mesenchymal Stem Cells Have a Modest Positive Effect on Angiogenesis in Hindlimb Ischemia - Chua, Kenon; Lim, Fui Ping; Lee, Victor Kwan Min; Phan, Toan Thang; Tai, Bee Choo; Tan, Yih Kai (Frontiers in Cell and Developmental Biology, 2021)
Purpose: We investigated the use of novel cells, the Cord Lining Mesenchymal Stem Cells (CL-MSCs) (US Patent number 9,737,568), in hind limb ischemia in a rabbit model and evaluated the potential of them in stimulating neovascularization. Methods: Twenty rabbits were divided into two separate groups. After the establishment of chronic hindlimb ischemia model, and at 21 days and 49 days post-operatively, animals in treatment group were injected with CL-MSCs (500,000 cells per 0.2ml on each site) at 10 different sites (Quadriceps- 4 sites, Hamstrings- 4 sites and Calf - 2 sites) of the ischemic left hindlimb muscles. The control group received only saline injection to the corresponding sites in the ischemic left hindlimb muscles, at the same time point as treatment group. Results: We found a higher number of CD31 positive cells in the treatment group, with a greater number of capillaries found in the treated muscles. The Rectus Femoris demonstrated a median vessel count/muscle fibre of 0.121 for the treatment group, compared to 0.076 in the control group (median difference 0.04; 95% CI 0.001 to 0.11; p=0.041). The Gastrocnemius demonstrated a median vessel count/muscle fibre of 0.175 for the treatment group, compared to 0.089 in the control group (median difference 0.087; 95% CI -0.006 to 0.234; p=0.07). Blood perfusion quantification through Laser Doppler Perfusion Imaging (LDPI) also demonstrated a non-statistically significant increase in perfusion in favor of the treatment group. CL-MSCs demonstrated no toxicity associated morbidity and minimal local immune reaction to implantation. Conclusion: CL-MSCs have a positive effect on angiogenesis in a rabbit hindlimb ischemia model. This preliminary data is encouraging and paves the way for future large animal studies or for clinical trials.